(untitled) (Biological Sciences - PJSIR, 2003)
Chalcones constitute an important group of natural products and some of them possess a wide range of biological activities such as antibacterial, anti-fungal, anti-inflammatory, antimi- crobial, anti-cancer, anti-tumour, postaglandin binding and insect anti-feedant (Hossain 2001).Carum carvi L. is reported for its medicinal values (Kirtikar and Basu 1995). In this paper, we describe the isolation of a flavone from the methanolic extract of the seeds of Carum carvi L. and its characterization as 4’, 5, 7-trihydroxy-2’-methoxyflavone (structure as given below).